Pengembangan Bahan Ajar Segitiga Dengan Pendekatan Open Ended Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika - Dian Mayasari (Jurnal Inovasi Matematika, 2019)
This study aims to develop a learning device by usingapproach open-endedis good (valid, active and effective) to improve students' mathematical problem solving usingapproach. open endedTeaching material developed in the form of teacher books, student books. Student activity sheet, RPP. The development of teaching materials using theapproach open-endedand referring to the modified model of Thiagarajan 4-D teaching materials, namely defining, designing, developing and distributing. The results of the study showed that the teaching materials developed had the value of validity, practicality, teacher response, student response and the results of field trials. Based on the results of field trials, teaching materials developed using an open-ended approach can improve students' mathematical problem-solving abilities so that their learning outcomes are better, from these results it is suggested that open ended approaches should be applied to schools.